Granjinhas escolares e a educação como a vida: apropriações do método de projeto na experiência da Fazenda do Rosário (1957-1969) - Pedro Henrique Oliveira Guimarães (2020)
The "Granjinhas" schools from Fazenda do Rosário, Ibirité, Minas Gerais, idealized by psychologist and teacher Helena Antipoff (1892-1974), and medical and teacher of Natural Sciences, Henrique Marques Lisboa (1876-1967), were developed from 1957 as pedagogical practices integrated into courses for the training of specialists in rural education of the Instituto Superior de Educação Rural - ISER, offered in the intern modality. It aimed, by scientific means, to experience the daily rural practices in the courses curriculum, where studies were carried out involving different knowledge developed in a rural property, such as: study of the land available for vegetables garden, for example. By means of the analysis and triangulation of sources on the subject, in an approach to the case study, the aim was to establish relationships between the pedagogical proposal of the Granjinhas and the methodology of projects, disclosed in Brazil in the XX century. Sources were mainly found in the Centro de Documentação e Pesquisa Helena Antipoff – CDPHA,: institutional journals, such as Rural Message and Rural Small Message; diaries of former students; ISER publications such as Granjinhas report etc., as well as the publication that explicit the Project Method of Willian Heard Kilpatrick (1871- 1965), and the book of Fernando Sáinz Ruiz (1891-1957) El Método de Proyectos en las escuelas rurales. Possible interfaces between the foundations and theoretical perspectives of the Granjinhas pedagogical practical project method were investigated. It was verified that Kilpatrick, Fernando Sáinz as well as Marques Lisboa and Antipoff, shared the will to transform human pathways by means of real activities, which stimulated apprentices autonomy in their own realities. Supported by the perspectives of interest and effort that founded the functionalist ideas of John Dewey (1859-1952), Kilpatrick presents the Project Method in 1918 as a proposition of practical materialization of these ideas, in order to make learning active and interested. In order to conceive an intentional activity in a social situation, a unit of this activity, in an interest with a purpose, Kilpatrick opposes the artificiality of the traditional school and approximates the reality, in a perspective of active education. To Kilpatrick, a project would have a real purpose, which would support teaching procedures and offer real motivations for learning. It would be a work plan that would position the student, voluntarily, in micro realities, based on propositions and experienced problems. Data show that the Granjinhas developed 8 pedagogical practices that would make the most of the environmental resources. The students had a leading role in solving rural problems; demarcating land available so that they could study them; extract from them the possibilities of reflections and social conviviality capable of subsidizing exchanges of knowledge and new learning. As pedagogical practices involved problems of one's own life as a school procedure, to the extent that educational activities are associated with common community activities. It is possible to conclude that these spaces developed an integral formation, in a regime of collaboration between the members of a given community, which approaches the suppositions of renewed education, from a progressive North American perspective, from which Dewey and Kilpatrick are representatives, as much as an European perspective, especially the Jean-Jacques Rousseau Institute where Helena Antipoff graduated and acted, becoming a disseminator.